Critical Analysis of Grievous Hurt Section 320, 326, IPC: A Case Law (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
Any hurt which endangers life or which causes the sufferer to be during the space of twenty days in severe bodily pain, or unable to follow his ordinary pursuits come under Clause “Eighthly” of Section 320 IPC defining “Grievous Hurt”. Section 326 IPC provides punishment for voluntarily causing grievous hurt by dangerous weapons or means like by fire, any corrosive substance, any heated substance etc. The fact of case was that the accused-appellant and the injured victim Sunil Kumar (PW-1) were neighbours. On 26.11.1997 at about 6 p.m., the appellant along with his wife (accused No. 2) poured acid on the victim from a ridge on the left side of the road causing serious injuries over the head, neck, shoulder and other parts of the body of the victim. The accused persons were charge sheeted under Section 326 read with Section 34 IPC. The case was tried by the Judicial Magistrate First Class (JMFC) and appellant was convicted for the offence under Section 326 IPC and was sentenced to one year imprisonment with fine of Rs.5000. Appeals before Additional District Court & High Court were dismissed. Supreme Court heard appeal on the question of sentence and applicability of Section 320 IPC. This study deals with interpretation of ingredients of Section 320, 326, IPC vis-à-vis Acid Attack which will be helpful in dealing with medicolegal aspect on Acid Attack and its gravity.
Keywords: Acid attack; Grievous hurt; Enhance punishment; Severe pain; Ordinary pursuits